The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1088/0953-4075/30/11/018
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of K-shell ionization cross sections of Fe and Mn by electron impact

Abstract: Measurements of K-shell ionization cross sections of Fe and Mn targets by the impact of electrons of 6-25 keV energy have been carried out. In the experiments thin targets with thick aluminium foil substrates were used. The influence on the measurements of electrons reflected from the aluminium substrate has been evaluated and corrected by a detailed electron transport calculation. It is shown that the corrected K-shell ionization cross sections of Mn are in good agreement with existing experimental data. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
5
10
0
Order By: Relevance
“…Figure 4 displays our experimental results, the analytical formula of Casnati et al (1982), and numerical calculations of Mayol and Salvat (1990), Hippler (1990) and Segui et al (2002), as well as experimental data from other authors. For Fe (figure 4(a)), our results are in relatively good agreement with those of Luo et al (1997); the results of He et al (1996) are about 30% larger. Here our data lie between the calculations of Segui et al (2002) and the Mayol-Salvat model, although a slightly better agreement is found with the former calculation.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Figure 4 displays our experimental results, the analytical formula of Casnati et al (1982), and numerical calculations of Mayol and Salvat (1990), Hippler (1990) and Segui et al (2002), as well as experimental data from other authors. For Fe (figure 4(a)), our results are in relatively good agreement with those of Luo et al (1997); the results of He et al (1996) are about 30% larger. Here our data lie between the calculations of Segui et al (2002) and the Mayol-Salvat model, although a slightly better agreement is found with the former calculation.…”
Section: Resultssupporting
confidence: 89%
“…Here our data lie between the calculations of Segui et al (2002) and the Mayol-Salvat model, although a slightly better agreement is found with the former calculation. In the case of Mn (figure 4(b)), our results (solid circles) are in relatively good agreement with Hippler's theoretical model, while those of Shima (1980), Luo et al (1997) and Tang et al (1999) seem to agree more closely with the Mayol-Salvat model. Although somewhat obscured by the absolute uncertainties of our data, the agreement with the results from the DWBA calculations of Segui et al (2002) and Casnati et al (1982) is considered satisfactory.…”
Section: Resultssupporting
confidence: 86%
“…Values of the Handbook of Chemistry and Physics (Boca Raton, FL: Chemical Rubber Company) are used for Kshell ionization energies. Excellent agreement is obtained between values deduced from the expression proposed and cross sections measured precisely by Shima [30,31] and Luo et al [32][33][34][35][36] in the vinicity of the threshold. The accuracy is better than 10% in this range.…”
Section: Resultssupporting
confidence: 74%
“…U 4) [29]. Recent measurements of the K-shell ionization by electron impact near-threshold energy region have been performed [32][33][34][35][36]. These near threshold measured cross sections are in excellent agreement with the previous data which were precisely measured [30,31].…”
Section: Empirical Formulasupporting
confidence: 80%
“…Figures 1(a)-(c) compare the present K-shell (1s 1/2 ) EII cross section of the C, Al, and Fe atoms, respectively, with existing measurements by Tavara et al [30], Hink and Ziegler [31], Limandri et al [32], Ishii et al [33], Hoffmann et al [34], Kamiya et al [35], McDonald and Spicer [36], Scholz et al [37], He et al [38], Luo et al [39] and Llovet et al [40]. We also compare the present results with other empirical models such as the RBEB by Kim et al [17], the MUIBED by Patoary et al [26], and the DWBA results by Bote et al [6].…”
Section: Electron Impact Inner-shell Ionization Of Atomssupporting
confidence: 67%